Kepercayaan dan Dukungan Teknologi Informasi untuk Pengelolaan Pengetahuan dalam Berbagi Pengetahuan untuk Meningkatkan Inovasi dan Kinerja Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Purbandari, Theresia (Widya Warta, 2013)
This  study  discusses the  influence  of  human  factors  and  technological  factors  on knowledge sharing, the influence of knowledge sharing to increase firm innovation, and the influence of firm innovation to increase firm performance. Primary data of this research were collected directly from the respondents’ answers using questionnaires. The samples were middle-level managers of manufacturing companies listed in Indonesia Stock Exchange. SmartPLS was used to process the data. Hypothesis testing proved that the hypothesis  1b-1c and the 2-4 hypothesis were acceptable, while the hypothesis 1a was unacceptable. It was proveable that the shared vision, trust,  and  IT  support for  KM  had  significant positive  effect  toward  knowledge  sharing; knowledge  sharing  had  effect  to  increase  firm  innovation;  firm  innovation  had  effect  to increase firm performance; while, the open-mindedness had no effect toward knowledge sharing.